Prospective and Explicit Clinical Validation of the Ottawa Heart Failure Risk Scale, With and Without Use of Quantitative NT‐proBNP. (11th March 2017) - Stiell, Ian G.; Perry, Jeffrey J.; Clement, Catherine M.; Brison, Robert J.; Rowe, Brian H.; Aaron, Shawn D.; McRae, Andrew D.; Borgundvaag, Bjug; Calder, Lisa A.; Forster, Alan J.; Wells, George A.
Abstract: Objectives: We previously developed the Ottawa Heart Failure Risk Scale (OHFRS) to assist with disposition decisions for acute heart failure patients in the emergency department (ED). We sought to prospectively evaluate the accuracy, acceptability, and potential impact of OHFRS. Methods: This prospective observational cohort study was conducted at six tertiary hospital EDs. Patients with acute heart failure were evaluated by ED physicians for the 10 OHFRS criteria and then followed for 30 days. Quantitative NT‐proBNP was measured where feasible. Serious adverse event (SAE) was defined as death within 30 days, admission to monitored unit, intubation, noninvasive ventilation, myocardial infarction, or relapse resulting in hospital admission within 14 days. Results: We enrolled 1, 100 patients with mean (±SD) age 77.7 (±10.7) years. SAEs occurred in 170 (15.5%) cases (19.4% if admitted and 10.2% if discharged). Compared to actual practice, using an admission threshold of OHFRS score > 1 would have increased sensitivity (71.8% vs. 91.8%) but increased admissions (57.2% vs. 77.6%). For 684 cases with NT‐proBNP values, using a threshold score > 1 would have significantly increased sensitivity (69.8% vs. 95.8%) while increasing admissions (60.8% vs. 88.0%). In only 11.9% of cases did physicians indicate discomfort with use of OHFRS. Conclusion: Prospective clinical validation found the OHFRS tool to be highly sensitive for SAEs in acute heart failure patients, albeit with an increase in admission rates. When available, NT‐proBNP values further improve sensitivity. With adequate physician training, OHFRS should help improve and standardize admission practices, diminishing both unnecessary admissions for low‐risk patients and unsafe discharge decisions for high‐risk patients.